Pest categorisation of Aonidiella orientalis. (25th November 2022) - ; Bragard, Claude; Baptista, Paula; Chatzivassiliou, Elisavet; Di Serio, Francesco; Gonthier, Paolo; Jaques Miret, Josep Anton; Justesen, Annemarie Fejer; Magnusson, Christer Sven; Milonas, Panagiotis; Navas‐Cortes, Juan A; Parnell, Stephen; et al.
Abstract: The EFSA Panel on Plant Health performed a pest categorisation of Aonidiella orientalis (Hemiptera: Diaspididae), the oriental scale, for the EU. A. orientalis is a species mostly occurring in tropical and subtropical areas. It is not listed in Annex II of Commission Implementing Regulation (EU) 2019/2072. It is a polyphagous species, with hosts in more than 160 plant genera belonging to more than 70 families. Numerous important crops suffer economic losses from A. orientalis such as citrus, figs, mangoes, papayas, bananas, palms, tea and some ornamentals. A. orientalis has also been recorded on several other crops which are important for the EU such as cotton, apricots, peaches and grapes, but there are no records of economic impact on these hosts. This scale insect reproduces rapidly and may reach high population density between 15 and 30°C. In the tropics, the scale breeds continuously, generations overlap and all life stages coexist. In Queensland, Australia, A. orientalis can have up to six generations each year. The main natural dispersal stage is the first instar which crawls over the natal host plant or to adjacent host plants and can be dispersed further by wind. Plants for planting, vegetables, cut flowers and fruits provide potential pathways for entry into the EU. Between 1997 and 2019, the UK intercepted A. orientalis more than 120 times, most frequently on mangoes and guava fruit. Climatic conditions and host availability in southern EU MS are favourable for outdoor establishment. Phytosanitary measures are available to reduce the likelihood of entry and spread. The main uncertainties include the area of establishment and magnitude of impact. A. orientalis meets the criteria that are within the remit of EFSA to assess for it to be regarded as a potential Union quarantine pest.